2011
DOI: 10.1111/j.1365-2265.2010.03916.x
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide for the stabilization of acylghrelin in human blood collections

Abstract: Our data suggest that AEBSF addition to K(2) EDTA blood immediately after collection without plasma acidification, processing on ice and 14-day 70 °C storage is the best treatment for accurately quantifying acylghrelin in human plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…Immediately after withdrawal, AEBSF (dilution 1:100) was directly added to all blood samples to prevent des-acylation of AG (3, 35). Whole blood was carefully mixed by inversion and stored on water ice (4°C) until centrifugation at 2500 g at 4°C for 5min.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after withdrawal, AEBSF (dilution 1:100) was directly added to all blood samples to prevent des-acylation of AG (3, 35). Whole blood was carefully mixed by inversion and stored on water ice (4°C) until centrifugation at 2500 g at 4°C for 5min.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrochorlic acid was not added to collection containers for AG samples, as recent work demonstrates that it is not required. 20 GLP-1 (active) was assayed using an enzyme-linked immunosorbent assay (ALPCO Diagnostics, Salem, NH, USA). To minimize inter-assay variability, all pre-measurement and post measurements for each subject were analyzed on the same plate.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, given the post-hoc nature of this study, samples were not pretreated with protease inhibitor. While results were expressed as %Δ, on the other hand future prospective studies with plasma pretreated with protease inhibitor [for details, see: (Blatnik and Soderstrom, 2011)] are needed to validate our preliminary findings. Finally, human studies in the context of alcohol use have shown a possible role of other feeding peptides such as leptin, adiponectin and resistin in alcoholism (Hillemacher et al, 2007; Hillemacher et al, 2009).…”
Section: Discussionmentioning
confidence: 89%